Chronic subdural hematoma that may be caused by nephrotic syndrome: a case report and literature review - Xue, Hang; Xue, Kun; Wang, Xiaohui; Xu, Weidong; Zhang, Weitao; Xia, Guangwen (Frontiers in Neurology, 2024)
Chronic subdural hematoma (CSDH) is a common complication of neurosurgery. Craniocerebral trauma is the likely cause. There are no reports relating CSDH with nephrotic syndrome. Its pathogenesis is very rare, and there are no previous reports on treatments for this disease. We report a case of chronic subdural hematoma that may be caused by nephrotic syndrome and review the previous literature on this subject.Chronic subdural hematomas are rarely caused by nephrotic syndrome. Trepanation and drainage may be considered for patients confirmed to have adequate hematoma liquefaction on imaging and who can tolerate craniotomy. Atorvastin should be supplemented as prophylactic treatment after the operation. Nephrotic syndrome should be treated as soon as the patient’s neurological condition is stable.